Liquid biopsy can cure early colorectal cancer recurrence – Case Report - Baraniskin, Alexander; Baba, Hideo A.; Theegarten, Dirk; Mika, Thomas; Schroers, Roland; Klein-Scory, Susanne (Frontiers in Oncology, 2023)
In the context of colorectal cancer (CRC), circulating tumor DNA (ctDNA) is frequently used to monitor the minimal residual disease (MRD). ctDNA has become an excellent biomarker to predict which patients with CRC are likely to relapse due to the persistence of micrometastases. MRD diagnosis via analysis of ctDNA may allow much earlier detection of relapse compared with conventional diagnosis during follow-up. It should lead to an increased rate of curative-intended complete resection of an asymptomatic relapse. Besides, ctDNA can provide crucial information on whether and how intensively adjuvant or additive therapy should be administered. In the present case, analysis of ctDNA gave us a crucial hint to the use of more intensive diagnostics (MRI and Positron emission tomography–computed tomography PET-CT) which led to earlier detection of CRC relapse. Metastasis detected early are more likely to be completely resectable with curative intent.